ANALISIS POTENSI SUMBERDAYA LAHAN UNTUK PERENCANAAN PENGEMBANGAN KOMODITAS UNGGULAN PERKEBUNAN DI KABUPATEN BANYUWANGI - mubekti, Mubekti (Jurnal Rekayasa Lingkungan)
Land is limited and non-renewable resource, on the other hand, people who need the land for development grow quickly. This paper discuss about the evaluation of land resource for plantation estate development planning in Banyuwangi District. General information regarding to physical environment are presented in order to know an overview of the study area. The Methodology of land suitability classifi cation corresponding to the selected plantation crops are briefl y explained, then, the results of the study are discussed. The study area consist of 9 physiographic spread from the fl at slope near the cost and verysteep slope near the mountain. Based on the land physical evaluation shows that the parent materials of the land are dominated by volcanic and lime stone. The results of the suitability classifi cation indicate that coconut crop could grow well in most of the plain up to undulating area. The land which suitable for coffee, clove and Vanilla cultivation are very small compared to the total of the study area and they are mostly located in the middle of the study area. Limiting factors of land suitability are mainly very diffi cult to upgrade, such us steep slope, soil effective depth, soil porosity, and drainage. In general, Banyuwangi District has a high potency of land for plantation estate extension.Keywords: land suitability, plantation estate, GIS, agriculture